2013
DOI: 10.1007/s12034-013-0486-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of power variation on wettability and optical properties of co-sputtered titanium and zirconium oxynitride films

Abstract: The present paper deals with deposition of titanium and zirconium oxynitride films prepared from cosputtering titanium and zirconium targets by reactive RF magnetron sputtering. The effect of power variation on various properties of the deposited films is analysed. The film gets transformed from amorphous to well crystalline oxynitride films with gradual increase of target powers as observed from XRD graphs. The films exhibit hydrophilic and hydrophobic behaviours depending upon the presence of various phases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In the films deposited at lower pressure of 0.7 Pa with supported discharge, the onset of crystallinity starts at the power of 80 W with a preferred orientation of (0 0 2), while no crystallinity has been observed in the films prepared at 60 W. Further increase in power to 100 W resulted in another preferred orientations of (1 0 0) along with (0 0 2). At a power of 120 W, the intensity of the peaks increased with the appearance of (1 0 1) peak [20]. Similar results were obtained by Chawla et al [9] who prepared Ti thin films by DC magnetron sputtering at substrate temperature of 200°C.…”
Section: Structural Analysissupporting
confidence: 84%
“…In the films deposited at lower pressure of 0.7 Pa with supported discharge, the onset of crystallinity starts at the power of 80 W with a preferred orientation of (0 0 2), while no crystallinity has been observed in the films prepared at 60 W. Further increase in power to 100 W resulted in another preferred orientations of (1 0 0) along with (0 0 2). At a power of 120 W, the intensity of the peaks increased with the appearance of (1 0 1) peak [20]. Similar results were obtained by Chawla et al [9] who prepared Ti thin films by DC magnetron sputtering at substrate temperature of 200°C.…”
Section: Structural Analysissupporting
confidence: 84%
“…20,21,23,25,27 While oxynitride phases have been observed in the as-deposited films in some cases, 26,30,31 several factors such as total pressure, power, and substrate temperature during sputtering are likely to simultaneously control both the composition and crystal structure of the as-deposited oxynitride chemistries. To decouple the temperature-dependent reactivity of the growing film in sputter atmosphere and thermally activated crystallization, we demonstrate RTP as postdeposition, iso-compositional crystallization process that provides access to high-temperature phases without compromising anion stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and zirconium oxynitride films are composed of a mixture of oxides, nitrides, and carbides, which gives them unique surface properties that can be tailored to specific applications. Rawal’s group [ 59 ] conducted a study on the deposition of TiNO and ZrNO mixture films using the co-sputtering of titanium and zirconium targets with reactive RF magnetron sputtering on Corning1737 glass substrates. The films were found to be sensitive to the power variation of both targets, and it was observed that the structure of the film changed from amorphous oxide to oxynitride films as the power increased.…”
Section: Oxide Hydrophobic Thin Filmsmentioning
confidence: 99%